A collaborative apparel new product development process model using virtual reality and augmented reality technologies as enablers. Issue 1 (2nd January 2019) - De Silva, R. K. J.; Rupasinghe, T. D.; Apeagyei, P.
ABSTRACT: This study presents a collaborative new product development (NPD) process model that accommodates different perspectives of stakeholders in an apparel value chain and expedites robust new product outcomes. Advanced technologies are demanded to establish such collaborative NPD process models. Virtual reality (VR) and augmented reality (AR) technologies have become prominent in product realisation during this process, to evaluate multiple alternatives. The study proposes a twofold approach where, in the first phase, a qualitative study was carried out to evaluate the viewpoint of value stream collaborators to study the potential opportunities and limitations of applying VR and AR in NPD process. In the second phase, a quantitative study was carried out to assess the apparel consumers' awareness on VR or AR applications, perceptions on such technologies, and intention to use such technologies in the context of apparel business. Data collection consisted of 10 in-depth interviews with experts in the industry and 94 survey responses from apparel consumers in the United Kingdom. It is concluded that VR and AR technologies will be enablers for NPD's success in the apparel industry in providing quick responses to consumers to enhance the performance of the new products.